Synthesis, structure and reactivity of transition metal complexes containing P-, O- and N-donor ligands. - Kuznetsov, Vladimir F. (University of Ottawa (Canada), 2001)
Rhodium complex, [Rh2(PPh3)4(mu-OH) 2] containing bridging hydroxo ligands, smoothly reacts with [HM(CO) 3Cp] (M = Cr, Mo, W) to afford the corresponding heterobimetallic complexes, [(Ph3P)2Rh(mu-CO)2M(CO)Cp]. The reaction of [Pd2L2(Ph)2(mu-OH) 2] with an equimolar amount of [HM(CO)3Cp] gives the organometallic hydroxo clusters [L2Pd2(Ph)2(mu-OH)(mu-CO) 2(mu3-CO)MCP] in high yield. These reactions can be regarded as the neutralization of an acidic transition metal hydride by a basic transition metal hydroxide. The structure of the Pd2Cr cluster was determined by single crystal X-ray diffraction study. The trinuclear hydroxo clusters are stable in the solid state but slowly decompose in solution, the decomposition path being strongly dependent on the nature of M. Facile and selective decomposition of the Pd2W hydroxo complex resulted in the formation of [Pd2(PPh3)2(Ph)2(mu-OH) 2], biphenyl, and the tetranuclear Pd2W2 cluster. Similar tetranuclear clusters were obtained in high yield when the palladium hydroxo dimers were neutralized with excess [HM(CO)3CP] or [HM(CO) 3Cp*]. However these reactions proceed by a different pathway involving Ph/H exchange process, and resulted in the formation of benzene and [PhM(CO) 3Cp] or [PhM(CO)3Cp*], respectively. Labeling experiments suggested that the H atoms of the hydrido and hydroxo ligands underwent an exchange which was faster than the neutralization and the concomitant formation of the metal-metal bond. Infrared and NMR studies show that the structures of the trinuclear hydroxo clusters were more rigid than those of the tetranuclear species. Tetranuclear complexes containing three different metals, Pd 2MoW and Pd2CrW were prepared and characterized. The reaction of [Rh(CO)(PPh3)2Cl] with the sodium salt of (1S, 2R, 5S)-menthol (NaOMent) cleanly affords chiral rhodium carbonyl alkoxo complex, [Rh(CO)(PPh3)2OMent], which was characterized by single crystal X-ray diffraction. The similar reaction of [Rh(PPh3) 3Cl] with NaOMent leads to the formation of [Rh(PPh 3)3H], apparently due to fast decomposition of the intermediate rhodium phosphine alkoxo complex via beta-H elimination. The reaction of [Rh(PPh3)3Cl] with NaOAr in toluene cleanly affords the corresponding aryloxo complexes [Rh(PPh3) 3(OAr)] (4.1). In solution 4.1 exists in equilibrium with PPh3 and the corresponding [Rh(PPh3)2(pi-OAr)] (4.2) The addition of HOAr shifts the equilibrium completely toward the corresponding adducts 4.2 · 2HOAr due to hydrogen bonding between the oxygen atom of the pi-coordinated OAr ligand and two molecules of HOAr. (Abstract shortened by UMI.)
Keywords: Chemistry, Organic.